Favoriser l’éveil à la démarche philosophique par une pédagogie de l’instant et une réciprocité dans les pratiques réflexives entre enseignants et élèves - Emmanuel Nal (Éducation et Socialisation)
A way to use children capacities to question and to put in question could be a reflexivity initiation, in the ordinary school time. By trying to practice it with the teacher and other pupils in the collective-class, the child can live the reciprocity on it: we can learn from each other - by mutual lightings - as we can learn of ourself, when the reflexivity allows us to reflect about our practices and to put into words our hidden knowledges and opinions. An initiation into the reflexivity, by the "educative" reciprocity it establishes, puts on the way of ethics of relation, critical mind and can provide a interessant complementarity with the DVP and other types of philosophical practices.